Solid-State P NMR, Far-IR, and Structural Studies on Two-Coordinate (Tris(2,4,6-trimethoxyphenyl)phosphine)copper(I) Chloride and Bromide - Bowmaker, Graham A.; Cotton, John D.; Healy, Peter C.; Kildea, John D. (American Chemical Society, 1989)
The reactions of acetonitrile solutions of copper(I) chloride, CuCl, and copper(I) bromide, CuBr, with the sterically hindered, highly basic tertiary phosphine ligand tris(2,4,6-trimethoxyphenyl)phosphine [=P(2,4,6)3] have been shown to form 1:1 monomeric adducts, [P(2,4,6)3 cux],The two compounds are isomorphous, crystallizing in the tetragonal space group P42. for the chloride, a = 15.237 (4) A, c = 12.373 (3) A, Z = 4, and R = 0.029 for 2339 “observed” (/ > 3<r(/)) reflections, while for the bromide, a - 15.312 (8) A, c = 12.457 (6) A, Z = 4, and R = 0.052 for 2148 “observed” reflections. Cu-P is 2.177 (1) A and Cu-Cl is 2.118 (2) A in the chloro compound; for the bromide, Cu-P is 2.197 (3) A and Cu-Br is 2.259 (2) A. In both complexes, the copper atom is displaced toward the nearest o-methoxy oxygen with Cu—O = 2.629 (4) (Cl) and 2.628 (7) A (Br); P-Cu-X angles are 172.97 (6) (Cl) and 172.00 (9)° (Br). Far-infrared spectra show' expected strong y(Cu-Cl) and ^(Cu-Br) bands at 355 and 262 cm-1, respectively. Strong bands in the range 90–100 cm-1are assigned to <5(P-Cu-X) bending modes. No bands assignable to v(Cu-P) modes were observable. The solid-state31P NMR spectrum of the ligand is characterized by a single line at -73 ppm (with respect to 85% H3P04). The spectrum for each complex shows an asymmetric quartet centered at -65 ppm with highly asymmetric line spacings of 1.40, 2.21, and 2.50 kHz and 1.48, 2.17, and 2.43 kHz, respectively. These data have been used to estimate copper nuclear quadrupole coupling constants for the two compounds.